Multiparametric Magnetic Resonance Imaging Improves the Prognostic Outcomes in Patients With Intrahepatic Cholangiocarcinoma After Curative-Intent Resection - Li, Qian; Wei, Yi; Che, Feng; Zhang, Tong; Yao, Shan; Zhao, Jian; Zhang, YuHui; Tang, Hehan; Song, Bin (Frontiers in Oncology, 2022)
Purpose: The prognosis of patients with intrahepatic cholangiocarcinoma remains unclear. Thus, this study was aimed to investigate whether additional multiparametric magnetic resonance imaging (mpMRI) would guide additional treatment and improve the prognostic outcomes of intrahepatic cholangiocarcinoma patients. Methods and Materials: This retrospective study included 256 patients undergoing dynamic enhanced computed tomography scan only (CT group) and 31 patients undergoing both mpMRI and computed tomography scans (CT+MR group). Propensity score matching (PSM) was used to minimize the potential selection bias and confounding effects. The overall survival (OS) and recurrence-free survival (RFS) rates were compared between the two groups. Results: More nodules (n=6), additional biliary dilation (n=4), and peritumoral parenchymal arterial phase hyperenhancement (n=18) were found with the additional mpMRI scan, which led to treatment modification. Cox regression analysis revealed the survival advantage of additional mpMRI imaging based on the OS (HR 0.396, 95% CI 0.239–0.657, P<0.001; PSM HR 0.400, 95% CI 0.218–0.736, P=0.003) and RFS (HR 0.558, 95% CI 0.352–0.882, P=0.013; PSM HR 0.508, 95% CI 0.288–0.897, P=0.020). Conclusions: Additional mpMRI helps clinicians to select better treatment options, lower the risk of tumor recurrence, and improve the overall survival.